Incidental Histopathologic Findings of Uterine Leimyosarcoma in a 58-year-old Woman: A Rare Case Report - Paskarani, Putu Erika; Hutapea, N. Yuliance Nurhawati; Widiyanti, Endang Sri; Nini, Cheryl; Sinaga, Naomi Juliana (Indonesian Journal of Cancer, 2025)
Introduction: Leiomyosarcoma accounts for (~40–50%) of all uterine sarcomas, but only 1-2% of all uterine malignancies. The incidence of leiomyosarcoma increases with age, reaching its peak in the seventh decade of life. Here, we proposed the importance of macroscopic and microscopic criteria of leiomyosarcoma to ensure clinical diagnosis.Case Presentation: A 58-year-old woman came with vaginal bleeding for 3 weeks before admission to the hospital.  The ultrasonography (USG) examination showed enlargement of the uterus and was clinically diagnosed as a leiomyoma. However, on histopathological examination, a proliferation of anaplastic cells was revealed, forming fasciculi that intersect each other and infiltrate into the connective tissue stroma. Mitosis 15/50 HPF and abnormal mitosis with abrupt coagulative necrosis are easily found. The histopathologic examination concluded that the patient had uterine leiomyosarcoma (pT1a), FIGO stage 1B.Conclusion: Histopathological examination and a clinicoradiological approach are key to identifying leiomyosarcoma. In most cases, although it is confined to the uterus, it has a poor prognosis. Otherwise, this case has a more favorable outcome due to the pathological and clinical stage, with 5-year survival rates of 40 – 70%